2019
DOI: 10.5902/1980509833080
|View full text |Cite
|
Sign up to set email alerts
|

Leaf structural traits of three species of <i>Qualea</i> Mart. (Vochysiaceae) in a cerradão area in the Cerrado-Amazonian Forest transition

Abstract: Qualea é um gênero comumente encontrado em diferentes fisionomias do cerrado brasileiro, crescendo em ecossistemas abertos até áreas florestais fechadas, sujeitos à alta irradiância, incêndios, baixa disponibilidade de nutrientes e deficit hídrico sazonal. Comparam-se aqui, atributos estruturais foliares de Qualea grandiflora Mart., Qualea multiflora Mart., e Qualea parviflora Mart., em uma área de cerradão na transição entre os biomas Cerrado-Amazônia. Amostras foliares foram coletadas na Reserva Biológica Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…In the same region and similar forest types of our study, other studies have also found anatomical variations in understory species related to environmental conditions, though with overall low plasticity index (Ariano & Silva 2016;Dardengo et al 2017;Rocha et al 2019;Müller et al 2020). On the other hand, in savannas and cerrado phytophysiognomies in the Cerrado-Amazon transition of Mato Grosso State, some studies revealed phenotypic plasticity with high occurrence of xeromorphic anatomical traits in most species (Simioni et al 2017;Pessoa et al 2019). It is well known that leaf anatomical traits vary among species, according to their ability to acclimation and intensity of light received (e.g., Rozendaal et al 2006;Markesteijn et al 2007;Liu et al 2019).…”
Section: Discussionsupporting
confidence: 79%
“…In the same region and similar forest types of our study, other studies have also found anatomical variations in understory species related to environmental conditions, though with overall low plasticity index (Ariano & Silva 2016;Dardengo et al 2017;Rocha et al 2019;Müller et al 2020). On the other hand, in savannas and cerrado phytophysiognomies in the Cerrado-Amazon transition of Mato Grosso State, some studies revealed phenotypic plasticity with high occurrence of xeromorphic anatomical traits in most species (Simioni et al 2017;Pessoa et al 2019). It is well known that leaf anatomical traits vary among species, according to their ability to acclimation and intensity of light received (e.g., Rozendaal et al 2006;Markesteijn et al 2007;Liu et al 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Understanding how functional attributes explain the occurrence of plants in landscapes with different types of vegetation, such as forests and savannas co-occurring within the limits of the Cerrado-Amazon transition (Maracahipes et al, 2018;Pessoa et al, 2019), as well as enclaves of Cerrado within the Amazon itself, is a challenge for botanists and ecologists (De Carvalho & Mustin 2017;Devecchi et al, 2020). Studies investigating the occurrence of secretory structures are ideal for understanding the mechanisms of acclimatization, adaptation and resistance of plants in different environments (Bezerra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%